STRATEGI KIAI DALAM MENSUKSESKAN PEMBELAJARAN NAHWU DAN SHOROF DI PONDOK PESANTREN AL-BIDAYAH TEGALBESAR KALIWATES JEMBER - Imam Wahyono (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
In studying the yellow book (kitab kuning) there is at least grammatical science that must be learned by a student, namely the science of Nahwu and Shorof. But in reality for the majority of students studying both sciences is a scourge. This is because in learning science nahwu and shorof there are many terms that seem difficult to understand. To induce the learning of nahwu and shorof, of course the existence of the kiai in determining his learning strategy is very important so that the presumption of learning nahwu and shorof that seems difficult can be easy. This study aims to determine the strategy of the kiai in inducing learning from nahwu and shorof at Al-Bidayah Islamic Boarding School in Tegalbesar Kaliwates Jember. The method used in this study uses a descriptive qualitative research approach. The data collection techniques using interviews, observation and documentation using purposive sampling in determining research subjects. Data analysis and checking the validity of the data in this study used the theory put forward by Miles and Huberman. In testing the validity of the data obtained, researchers used a triangulation technique. This research has concluded that the kiai in the success of nahwu and shorof learning use two strategies, namely the learning method and the preparation of textbooks. The method that is often used is the Wetonan method, sorogan and memorization (hafalan) as traditional methods and peer tutorial methods as modern methods. The preparation of textbooks done by the kiai is a new breakthrough because this book is arranged systematically so that it is easy to understand, digest and understand by students. Keywords: Strategy of the kiai, the science of Nahwu and Shorof